Conjugate heat transfer and melting behaviour of Nano particle added phase change materials in a thick concave walled chamber - Rajesh, Vemula; Öztop, Hakan Fehmi (Elsevier, 2025)
In this paper, a comprehensive computational study is carried out to explore the phase-change dynamics and conjugate heat transfer in a chamber filled with NEPCM-water nanofluid. The chamber features curved (concave type) thick solid walls, and the coupled heat transfer between the solid and fluid regions is modelled using the robust finite element method. The effect of key dimensionless parameters including the thermal conductivity ratio (Rk), Stefan number (Ste), Rayleigh number (Ra), NEPCM nanoparticle volume fraction (phi), and fusion temperature (theta f) is studied on streamlines, isotherms, and heat capacity contours along with average Nusselt number. The results reveal that higher Rayleigh numbers and lower Stefan numbers enhance natural convection and broaden NEPCM activation zones. An intermediate fusion temperature of theta f = 0.3 consistently yields optimal thermal performance by aligning the melting range with dominant thermal gradients across all conductivity ratios. Increasing NEPCM volume fraction leads to a uniform rise in average Nusselt number, while the balanced conductivity case (Rk = 1) enables the most effective utilization of latent heat. These findings provide critical insights for optimizing NEPCM-based thermal energy storage and passive cooling systems in enclosures with complex thermal boundaries.
Keywords: NEPCM-water nanofluid; Conjugate heat transfer; Phase change material (PCM); Fusion temperature; Stefan number; Natural convection in enclosures